Consensus-based classification system for intra-operative management of labral tears during hip arthroscopy—aggregate recommendations from high-volume hip preservation surgeons. Issue 4 (19th May 2021) - Lall, Ajay C; Annin, Shawn; Chen, Jeff W; Diulus, Samantha; Ankem, Hari K; Rosinsky, Philip J; Shapira, Jacob; Meghpara, Mitchell B; Maldonado, David R; Hartigan, David E; Krych, Aaron J; Levy, Bruce A; et al.
Abstract: The purpose of this study was to survey high-volume hip preservation surgeons regarding their perspectives on intra-operative management of labral tears to improve decision-making and produce an effective classification system. A cross-sectional survey of high-volume hip preservation surgeons was conducted in person and anonymously, using a questionnaire that is repeated for indications of labral debridement, repair and reconstruction given the torn labra are stable, unstable, viable or non-viable. Twenty-six high-volume arthroscopic hip surgeons participated in this survey. Provided the labrum was viable (torn tissue that is likely to heal) and stable, labral debridement would be performed by 76.92% of respondents for patients >40 years of age and by >84% of respondents for stable intra-substance labral tears in patients without dysplasia. If the labrum was viable but unstable, labral repair would be performed by >80% of respondents for patients ≤40 years of age and > 80% of respondents if the labral size was >3 mm and located anteriorly. Presence of calcified labra or the Os acetabuli mattered while deciding whether to repair a labrum. In non-viable (torn tissue that is unlikely to heal) and unstable labra, labral reconstruction would be performed by 84.62% of respondents if labral size was <3 mm. The majority of respondents would reconstruct calcified and non-viable, unstable labra that no longer maintained a suction seal. Surgeons performing arthroscopic hip labral treatment may utilize this comprehensive classification system, which takes into consideration patient age, labral characteristics (viability and stability) and bony morphology of the hip joint. When choosing between labral debridement, repair or reconstruction, consensus recommendations from high-volume hip preservation surgeons can enhance decision-making.